Factors Related to Low Birth Weight Incidents in The Work Area of Tarus Public Health Center - Suharni M. Situmorang; Masrida Sinaga; Amelya B. Sir (Media Kesehatan Masyarakat, 2022)
Babies with Low Birth Weight (LBW) have a higher risk of impaired growth and development and even death than babies born with normal birth weight. This study aims to analyze the relationship between maternal age, parity, birth spacing, maternal disease during pregnancy, maternal nutritional status, and antenatal care with the incidence of LBW in the work area of Tarus Public Health Center, Kupang Regency. This research was quantitative using a case-control design. The population consisted of all babies born in November 2019 to May 2020. Case samples were 21 LBW infants and the control group had 21 normal birth weight infants. The statistical test used Chi-square with α=0.05. The results showed that maternal age, parity, maternal illness during pregnancy, maternal nutritional status, and antenatal care were related to the LBW incidence, while birth spacing was not associated with the incidence. Health workers need to continuously educate the community about preventing risky pregnancies, such as being too young (<20 years), too old (>35 years), and too many (parity>3), through the use of contraceptives, the nutritional needs of pregnant women, and routine pregnancy check-ups.